Teachers' Strategies and Obstacles in Developing English Language Skills in the Foreign Language Special Program at Muhammadiyah 1 High School in Surakarta - Widyaningtyas, Keyla Puspita; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2025)
This study explores the strategies used by teachers and the obstacles they face in developing students' English language skills in the Special Foreign Language Program at Muhammadiyah 1 Surakarta High School. English is taught as a foreign language in Indonesia, so its use outside the classroom is limited, creating challenges for students in mastering the four skills: listening, reading, speaking, and writing. The special foreign language program is designed to provide more intensive English language instruction, but its implementation still presents various difficulties for teachers, including differences in student motivation, limited learning resources, and classroom management issues. Using a qualitative case study approach, the research collected descriptive data through interviews, observations, and documentation. The findings identify commonly applied strategies such as task-based learning, cooperative learning, and project-based activities and reveal several obstacles, including differences in student motivation and ability, limited learning resources, and curriculum demands. These findings provide important insights for improving English language learning practices and strengthening the implementation of specialized language programs in secondary education.